2008
DOI: 10.1890/06-2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecotone Shift and Major Droughts During the Mid–late Holocene in the Central Tibetan Plateau

Abstract: A well-dated pollen record from a large lake located on the meadow-steppe ecotone provides a history of ecotone shift in response to monsoonal climate changes over the last 6000 years in the central Tibetan Plateau. The pollen record indicates that the ecotone shifted eastward during 6000-4900, 4400-3900, and 2800-1600 cal. yr BP when steppes occupied this region, whereas it shifted westward during the other intervals when the steppes were replaced by meadows. The quantitative reconstruction of paleoclimate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 48 publications
(60 reference statements)
2
72
0
1
Order By: Relevance
“…Some researchers suggested that precipitation plays a more important role than temperature in arid or semi-arid regions like the Tibetan Plateau (Sun et al 2013b). For example, monsoon precipitation controls vegetation distribution in summer (Shen et al 2008). In addition, no significant correlation has been found among the maximum vegetation index in growing season and temperature and precipitation across the Tibetan Plateau (Shen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that precipitation plays a more important role than temperature in arid or semi-arid regions like the Tibetan Plateau (Sun et al 2013b). For example, monsoon precipitation controls vegetation distribution in summer (Shen et al 2008). In addition, no significant correlation has been found among the maximum vegetation index in growing season and temperature and precipitation across the Tibetan Plateau (Shen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results of vegetation discriminant analysis showed that during 6~4.9, 4.4~3.9, and 2.8~1.6 ka BP, alpine steppe occupied the region caused by eastward shifts of the MSE, whereas alpine meadow became dominant when the MSE shifted westwards during 4.9~4.4, 3.9~2.8, and after 1.6 ka ( Fig. 3B) (Shen et al, 2008).…”
Section: Vegetation Changes Within An Eastewest Transectmentioning
confidence: 96%
“…Consequently, Cyperaceae-dominated alpine meadow is vulnerable to changes in precipitation (effective moisture) (Shen, 2003;Shen et al, 2008), while Artemisia-dominated steppe is sensitive to changes in temperature in the region Li et al, 2011).…”
Section: Climatic Implications Of Modern Pollen Distributionmentioning
confidence: 99%
See 2 more Smart Citations